STUDI LITERATUR: KOMPETENSI AUDITOR DAN KEAHLIAN SISTEM INFORMASI AUDITOR TERHADAP PEMBUKTIAN FRAUD - Rosyida, Isnaini Anniswati (Pro-fit, 2024)
This literature review discusses the application of financial financing and SWOT analysis in the digital creative industry in the Industrial Revolution 4.0 era. SWOT analysis and financial financing have become important tools for companies to understand the internal strengths, weaknesses, opportunities, and threats that affect their business. In the ever-growing digital creative industry, SWOT analysis plays a crucial role in helping companies identify weak points that need to be fixed and new opportunities that can be exploited. This literature review concludes that the effective application of SWOT analysis allows companies to develop relevant financial potential and position themselves to compete better in a competitive market. However, companies need to understand that SWOT analysis is a dynamic tool that requires continuous updating and adjustment according to changes in the business environment. Therefore, the advice for companies is to continuously monitor industry trends, develop a deep understanding of consumer needs and preferences, and invest in the development of relevant technical and creative expertise. Thus, companies can utilize SWOT analysis and financial financing effectively as an integral part of their strategy to maintain competitive advantage in the Industrial Revolution 4.0 era.